A Virus-Specific Immune Rheostat in the Immunome of Patients Recovering From Mild COVID-19 - Yeo, Joo Guan; Leong, Jing Yao; Tay, Shi Huan; Nadua, Karen Donceras; Anderson, Danielle E.; Lim, Amanda Jin Mei; Ng, Xiang Wen; Poh, Su Li; Guo, Dianyan; Yaung, Katherine Nay; Kumar, Pavanish; Wasser, Martin; et al. (Frontiers in Immunology, 2021)
Despite significant progress in our understanding of the pathogenesis of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the mechanisms of immune imbalance leading to diverse clinical fates remain to be elucidated. An accurate depiction of the convalescent COVID-19 immunome will help delineate the immunological milieu crucial for disease resolution and long-term protection. Using mass cytometry, we characterized the immune architecture in patients recovering from mild COVID-19. We identified a virus-specific immune rheostat composed of an effector T (Teff) cell recall response that is balanced by the enrichment of a highly specialized regulatory T (Treg) cell subset. Both components were reactive against a peptide pool covering the receptor binding domain (RBD) of the SARS-CoV-2 spike glycoprotein. We also observed expansion of IFNγ+ memory CD4+ T cells and virus-specific follicular helper T (TFH) cells. Overall, these findings pinpoint critical immune effector and regulatory mechanisms essential for a potent, yet harmless resolution of COVID-19 infection.